2008
DOI: 10.1007/s00595-007-3615-4
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of abdominal aortic aneurysm associated with polycystic kidney disease: Report of two cases

Abstract: An abdominal aortic aneurysm associated with polycystic kidney disease is a comparatively rare but quite important condition because treating this disease is difficult, especially regarding the aortic approach. We herein present two such patients who underwent a left nephrectomy followed by an aneurysmectomy which was reconstructed with a bifurcated prosthetic graft. In both cases, the left nephrectomy enabled us to obtain an adequate operative field to expose the abdominal aorta and the surgical procedures co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…8 Concurrent AAA is reported in 5% to 10% of ADPKD patients. [5][6][7] The basis of this relationship is still controversial. ADPKD often leads to renal dysfunction and hypertension, and some theorize that these complications can contribute to the formation of AAA.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…8 Concurrent AAA is reported in 5% to 10% of ADPKD patients. [5][6][7] The basis of this relationship is still controversial. ADPKD often leads to renal dysfunction and hypertension, and some theorize that these complications can contribute to the formation of AAA.…”
Section: Discussionmentioning
confidence: 98%
“…4 Abdominal aortic aneurysm (AAA) has been associated with ADPKD, with prevalence of AAA in ADPKD patients ranging from 5% to 10%, and the two conditions can significantly complicate operative management of each other. [5][6][7] …”
mentioning
confidence: 98%
“…Other vascular abnormalities have also been described in ADPKD, including intracranial dolichoectasia [32, 33], ascending aortic aneurysms [34], and dissections of the coronary [35, 36] and vertebral [37] arteries. It has also been suggested that ADPKD patients are at higher risk for AAA [38394041], although a systematic study found no increased risk of AAA in ADPKD patients compared to healthy family members [42]. …”
Section: Discussionmentioning
confidence: 99%